CD7 expression distinguishes subsets of CD4(+) T cells with distinct functional properties and ability to support replication of HIV-1. - Wallace, D; Matear, P; Davies, D; Hicks, R; Lebosse, C; Eyeson, J; Beverley, P; Vyakarnam, A (2000)
Enrichment of a subset of CD4(+)CD45R0(+)CD7(-) T cells has been observed in HIV-infected individuals. We have investigated the ability of CD7(+) and CD7(-) T cells to support replication of HIV and show that virus replicates preferentially in CD7(+) cells. Several possible mechanisms that may underlie such differences in susceptibility to HIV were studied. Our data demonstrate that mitogen stimulation induces poor expression of CD25 and IL-2 in CD7(-) compared with CD7(+) cells. We also show that uninfected CD7(-) cells are more resistant to mitogen-induced apoptosis than CD7(+) cells. Our data support the view that the CD7(-) subset is inherently resistant to HIV replication and that this is due in part to reduced CD25 expression and IL-2 production.